Optimization of mechanical input power to synchronous generator based on transient stability center-of-inertia: COI angle and COI speed - Hashim H. (2023)
Rotor angle of the machine may accelerate or decelerate due to transient instability depending on the mechanical power or the turbine power, P m and electrical power, Pe. As such, injecting an appropriate mechanical input power in accordance to the electrical power demand and losses at a critical time and condition will avoid major supply interruption due to unnecessary tripping of circuit breaker during transient instability. This paper presents Evolutionary Programming (EP) approach to optimize the mechanical input power in order to prevent transient instability in the system. The optimization is based on Area-based COI-referred Transient Stability Indexes: COI Angle and COI Speed, for a three area system with six generators. Results obtained from the experiment revealed that the EP approach is able to give an optimal solution. 2011 IEEE.